Is Operational Quality Parameters of Baldrige Award relevant in today scenario? Answered by South Indian Hospitality Industry - Jagannathan, Sekkizhar; R, Jagajeevan (Journal of Contemporary Research in Management (JCRM), 2017)
The Balridge award originated from the Malcolm Balridge National Quality Improvement Act, for development of guidelines and criteria's for evaluating their quality efforts. Performance are measured conventionally by financial and market performance. Some of the previous researchers fail to get or to link these variables. Therefore, three variables stability, structure and simplicity are taken as the performance indicators.Â  The Indian hospitality industry has emerged as one of the key industries driving growth of the services sector.Â  If the theoretical relationship can be established in this industry then it can be generalized for all service and manufacturing industries. The paper tries to find the relationship of the Operational parameters of the Balridge award and with the performance outcomes of stability, structure and simplicity which was originally used in age-old practices of US Training Within Industry (TWI) program. A set of structural relationship models have been analyzed in a scenario of hotel industry to validate the relationship. Primary data collected through a structured questionnaire in southern parts of India is used.